2017
DOI: 10.18203/2320-6012.ijrms20174561
|View full text |Cite
|
Sign up to set email alerts
|

Awareness regarding Janani Shishu Suraksha Karyakram (JSSK) among mothers: a community based cross-sectional study in rural area of Raipur district, Chhattisgarh

Abstract: Background: In order to increase accessibility of health care services for pregnant women and sick infants and to reduce out-of-pocket expenditure, Ministry of Health and Family welfare, Government of India has launched a nationwide initiative- Janani Shishu Suraksha Karyakram on June 01, 2011. The objective of the study was to find out the awareness level about the entitlements of JSSK among mothers with child less than one year and its association with different socio-demographic variables.Methods: A communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…15 Increasing parity was also found to be associated with good knowledge in the study from Raipur (Chhattisgarh). 12 The reason for the differences of findings with the present study might be that none of these studies conducted a multivariable analysis for finding out significant predictors after adjusting for confounders. Increasing parity might be increasing their contact with front-line health workers, who might be giving them information, leading to increased knowledge among the mothers.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…15 Increasing parity was also found to be associated with good knowledge in the study from Raipur (Chhattisgarh). 12 The reason for the differences of findings with the present study might be that none of these studies conducted a multivariable analysis for finding out significant predictors after adjusting for confounders. Increasing parity might be increasing their contact with front-line health workers, who might be giving them information, leading to increased knowledge among the mothers.…”
Section: Discussioncontrasting
confidence: 73%
“…A study from Chhattisgarh (central India) reported 59% good knowledge among post-natal mothers regarding JSSK, which was higher than the present study, the difference might be due to a different scoring pattern used in their study. 12 The lack of knowledge was cited as the commonest reason for non-utilization of maternity benefit schemes in Karnataka (southern India), suggesting the need to create awareness regarding JSSK among ante-natal as well as post-natal mothers. 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only 37.9% of beneficiaries could avail this service to reach the facility and 41.7% of beneficiaries back to home using this facility. Study conducted by Chandrakar et al [21] showed that maximum awareness (89.20%) regarding entitlements among mothers was seen for free transport services from home to health institutions, followed by the drop back transport facility from hospital to home (85.22%). The increase in use of ambulances while going back could be attributed to first exposure about such services in few cases from hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 63 (40%) had median OOP Rs 210 during hospitalization and 127 (81%) had median OOP of Rs 420 during transport. So it was concluded that JSSK benefitted the mothers utilising the public sector facilities however drugs, consumables and transport contributed to the out-of-pocket expenditure (Chandrakar et al, 2017).…”
mentioning
confidence: 99%